The Impact of Understanding Economic Literacy and Lifestyle on Entrepreneurial Intention of Students in Higher Education - Setiawan, Ananda; Soetjipto, Budi Eko; Rudijanto, Ery Tri Djatmika (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
The importance of understanding economic literacy, controlling lifestyle, and enhancing student entrepreneurial intentions should not be overlooked. This study aimed to determine the impact of understanding economic literacy and lifestyle on student entrepreneurial intentions. This research is included in a quantitative descriptive study using multiple regression analysis techniques. This study's population were all students of economic education at Lambung Mangkurat University, as many as 267 students. The sample size taken was 157 people by random sampling. The data collection technique used a questionnaire. This study's results indicate that students' economic literacy has a positive and significant impact on entrepreneurial intentions, lifestyle has a positive and significant impact on students' entrepreneurial intentions, and simultaneously economic literacy and lifestyle have a positive and significant impact on entrepreneurial intentions. The coefficient of determination of economic literacy and lifestyle on entrepreneurial intentions is 38%. From these results, it can be concluded that economic literacy and lifestyle positively and positively impact entrepreneurial intentions.Â